Symptoms of prenatal depression are associated with raised salivary alpha-amylase levels. (October 2015) - Braithwaite, Elizabeth C.; Ramchandani, Paul G.; Lane, Tracy A.; Murphy, Susannah E.
Highlights: Prenatal depression was associated with increased awakening sAA. In late pregnancy, depression was linked with elevated sAA throughout the day. All diurnal sAA measures were correlated with each other. Abstract: Purpose: Prenatal depression increases risk for a number of adverse offspring outcomes, however the biological mechanisms underlying this association remain unclear. It has been suggested that maternal glucocorticoids may mediate this link, though supporting evidence has been mixed. An alternative mechanism of effect may be via depression-induced changes in maternal sympathetic nervous system (SNS) function. We examined this hypothesis by determining the relationship between symptoms of maternal prenatal depression and diurnal salivary alpha-amylase (sAA) levels. Methods: 76 pregnant women were recruited during either the second or third trimester of pregnancy. Participants self-reported depressive symptoms using the Edinburgh postnatal depression scale. Saliva samples, to be assayed for alpha-amylase activity, were collected at home over two working days. Results: Participants with depressive symptoms in later pregnancy had elevated awakening sAA levels compared with non-depressed controls ( t (73)  = −2.737, p  = 0.008), and continued to have raised sAA throughout the day ( F (1)  = 10.924, p  = 0.002). Conclusions: Our findings highlight that symptoms of depression during late pregnancy are associated with increased maternal SNS activity. Thus, changes in maternal SNS function, which may include increased vasoconstriction and reduced foetal blood flow, could, in part, mediate associations between prenatal depression and adverse offspring outcomes.